PENGARUH KOMPETENSI, KOMUNIKASI INTERNAL DAN ETOS KERJA TERHADAP EFEKTIFITAS KERJA PEGAWAI PADA CABANG DINAS PENDIDIKAN ACEH KABUPATEN BIREUEN - Idayani Idayani; Mai Simahatie (IndOmera, 2026)
The purpose of this study is to test the effectiveness of employee work by considering the factors of competence, internal communication, and work ethics. This study was conducted on 46 employees of the Bireuen Regency Regional Education Office Branch, using an associative method with a quantitative approach using path analysis data analysis. The results of the study indicate that: (1) competence directly and together with internal communication and work ethics factors have a positive influence on work effectiveness of 56.16%. (2) Internal communication aspects have a direct and indirect influence with competence and work ethics factors on employee work effectiveness of 60.44%. (3) Meanwhile, work ethics have a direct and indirect influence together with competence and internal communication on work effectiveness of 62.2%. (4) Simultaneously, these three factors contribute to changes in employee work effectiveness of 72.1%. (5) There is a causal relationship between competence and internal communication aspects with a fairly strong category of 0.723, also a relationship between internal communication and work ethics with a very strong category of 0.833. Meanwhile, the relationship between work ethics and competency factors is also strong, at 0.802